2020
DOI: 10.1007/s00264-020-04482-4
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary fixation versus anatomically contoured plating of unstable ankle fractures: a randomized control trial

Abstract: Aim This study compared functional outcomes between anatomical shaped fibular plates and intramedullary nail fixation of adult patients who sustained unstable ankle fractures. Methods A prospective randomized control trial was conducted between November 2013 and December 2016 on patients that presented with an unstable ankle fractures. They were randomized into a plate-and-screw group and a fibula nail group. At each post-operative visit the wounds were reviewed, and specific outcome measures were recorded, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…In particular, the 3 randomized controlled trials available comparing the treatment of unstable ankle fractures with a fibula nail versus plate have demonstrated similar functional results with lower complication rates and less need for implant removal. 7,8,25 Much of the existing literature examined earlier nail designs without dedicated formal proximal fixation which resulted in poorer rotational and axial stability. This led to nail migration and malunion.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the 3 randomized controlled trials available comparing the treatment of unstable ankle fractures with a fibula nail versus plate have demonstrated similar functional results with lower complication rates and less need for implant removal. 7,8,25 Much of the existing literature examined earlier nail designs without dedicated formal proximal fixation which resulted in poorer rotational and axial stability. This led to nail migration and malunion.…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred and ninety-four patients were male (56%, range 37-86%, n = 528). Two papers reported the HIV status of patients (17% positive, 68% negative, 15% unknown, n = 110) [19,20].…”
Section: Demographics Of Patients and Injuriesmentioning
confidence: 99%
“…We found no differences in the range of motion between the intervention and control groups overall and between the ankle and tibial plateau fracture subgroups, our results are in line with other studies that reported the range of motion of the ankle and knee. [32][33][34][35][36] Our findings should be interpreted within the limitations of this study. The main limitation was the significant proportion of patients who dropped out.…”
Section: Discussionmentioning
confidence: 74%
“…We found no differences in the range of motion between the intervention and control groups overall and between the ankle and tibial plateau fracture subgroups, our results are in line with other studies that reported the range of motion of the ankle and knee. 3236…”
Section: Discussionmentioning
confidence: 99%